Eco-friendly QbD-optimized chromatographic method for simultaneous analysis of metronidazole and nicotinamide with applications in permeation, stability, and sustainability evaluation - Kanaka Parvathi Kannaiah; Mohamed A. M. Ali; Hemanth Kumar Chanduluru; Anis Ahmad Chaudhary; Mahmoud El-Maghrabey; Reem H. Obaydo; Galal Magdy; Mohamed A. El Hamd (BMC Chemistry)
Abstract Metronidazole (MTZ) and nicotinamide (NCT) are co-formulated in Anaero® gel to treat skin conditions like acne and rosacea through combined antimicrobial and anti-inflammatory effects. This study presents the first validated in vitro permeation test (IVPT) method using Franz cells to assess the gel’s drug release profile. Chromatographic separations were conducted with an RP-HPLC-photodiode array (PDA) system equipped with an ODS column using gradient elution of ethanol and phosphate buffer (10 mM, pH 3.5) at a flow rate of 1.0 mL/min. pre-optimized conditions were determined using a two-level full factorial design (23 FFD). The method demonstrated good linearity for MTZ (0.03 – 1.125 µg/mL) and NCT (0.6 – 6.0 µg/mL). The in vitro permeation curve, constructed by plotting mass flux in. μg/cm2.hour against mid-time in hours, showed similar permeation patterns for both drugs over time. The permeation coefficient (Kp) values for MTZ and NCT were 0.016 and 0.012 × cm−2. hour−1, respectively. Both compounds started permeating through the membrane within 5 min, indicating good permeation and the suitability of the formulated combination for drug release. This study presents the first IVPT method using Franz cells to assess Anaero® gel’s drug release profile. Additionally, the method was evaluated under various forced degradation conditions, confirming its stability and robustness. A low ethanol ratio was maintained throughout the short runtime, emphasizing the method’s eco-friendly design. To further support its sustainability, a comprehensive hexametric evaluation was conducted using multiple greenness assessment tools, including the Unified Greenness Principles (ChlorTox Scale), Green Engineering principles (Spider tool), Green and White Analytical Chemistry Principles (AGREE, Hexagon model, RGB12 Algorithm), and alignment with the UN Sustainable Development Goals (SDGs) via the NQS Indicator. The method was also fully validated following ICH Q2(R1) guidelines. A comparative assessment against 21 existing LC and UV methods revealed that the developed approach achieved the highest greenness score (0.75), required the least solvent volume (1.5 mL ethanol), and enabled sensitive detection of low-dose MTZ alongside high-dose NCT in semisolid gel matrices. These advantages underscore the method’s novelty, eco-efficiency, and analytical superiority.